Identity Formation and Developing Meaningful Social Relationships: The Role of the Polish Catholic Community for Polish Young People Migrating to Sweden - Shmulyar Gréen, Oksana; Melander, Charlotte; Höjer, Ingrid (Frontiers in Sociology, 2021)
This paper draws on the research project Transnational childhoods, illuminating the experiences of children and young people from Poland who go through transnational transitions (Pustulka and Trabka 2019) when they move to Sweden. For migrant children in our study it entails multiple changes and shifts aligned with their life course, including the initial parental migration, children’s own migration and reunification with parents and transitions to adulthood in transnational-, translocal- and local spaces. In this phase of life, young people are preoccupied in particular by identity-seeking and by creating new meaningful relationships. In the paper, we focus primarily on the experiences of young Polish migrants and analyse the interviews, build on network maps and life- lines. We examine what role the Catholic community in Sweden plays in relation to their identity building and the transitions to adulthood post-migration. Theoretically, we are inspired among others by the concept of lived religion, which focuses on the actual practices and relationships by which young people “make up their personal religious experience and expression “(McGuire 2008:2). Conducting the analysis of the empirical data we identify three important themes: 1) how young Poles talk about spirituality as an important component of their identity construction post-migration; 2) how the Catholic community becomes one of the main sources of building new relationships in Sweden; 3) how the places of worship and specifically significant religious leaders within the catholic community become important for the guidance in family relationships and future plans. The tentative results suggest that through faith and spiritual activities young migrants acquire resources to develop resilient responses to the challenges caused by migration. They gain social acceptance and belonging in the social sites, where communication in their native languages and a sense of familiarity help them to become vocal about their needs, rights and feelings.